Two Tectonic Geomorphology Studies on the Landscape and Drainage Network of Chain and Piedmont Areas of the Abruzzi Region (Central Apennines, Italy) - Enrico, Miccadei; Tommaso, Piacentini (IntechOpen, 2011)
None